Diphenyleneiodonium inhibits NF-κB activation and iNOS expression induced by IL-1β: involvement of reactive oxygen species - A. Ferreira Mendes; A. Pato Carvalho; M. Margarida Caramona; M. Celeste Lopes (Mediators of Inflammation)
Aims: In this work, we studied the mechanisms by which diphenyleneiodonium chloride (DPI) inhibits nitric oxide (NO) synthesis induced by the pro-inflammatory cytokine interleukin-1β (IL-1) in bovine articular chondrocytes. To achieve this, we evaluated the ability of DPI to inhibit the expression and activity of the inducible isoform of the NO synthase (iNOS) induced by IL-1. We also studied the ability of DPI to prevent IL-1-induced NF-κB activation and reactive oxygen species (ROS) production.